Healthcare telematic applications in Cyprus - Andreou, Andreas S.; Pattichis, Constantinos S.; Schizas, Christos N. (My University, 2002)
Objectives: a) To present a review of ongoing health telematic applications in Cyprus. b) To promote the use of these health telematic applications in the Cyprus region. c) To help in the spin off of other health telematic applications thus enabling the offering of a better health service to the citizens. Methods and Results: The health telematics applications include a medical system for emergency telemedicine (AMBULANCE and EMERGENCY-112 projects), a system for the evaluation of the risk of stroke by telemedicine (EROS), a diagnostic telepathology network in gynaecological cancer (TELEGYN), a collaborative virtual medical team for home healthcare of cancer patients (DITIS), and a health telematics training network (HEALTHNET). The paper refers to the set-up and characteristics of these applications and tries to relate them with the health policies that should be applied in Cyprus. Conclusions: It is anticipated that this paper will promote the importance of health telematics applications for Cyprus and increase the awareness on the possibilities that these applications offer for health policies in all levels of health related human resources.
Keywords: Medical informatics; Healthcare telematics